IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGEMBANGAN KARAKTER ANAK USIA DINI - Anggraini, Leza; Adinda Putri, Regina; Emelia, Rinda; Yusria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Independent Curriculum (Merdeka Curriculum) is a transformation in Indonesian education that provides flexibility for educational units to optimize student potential, including at the Early Childhood Education (PAUD) level. The primary focus of this curriculum is character development, culminating in the Pancasila Student Profile. This study aims to analyze the implementation of the Independent Curriculum in early childhood character development, the strategies used, and the challenges faced. The research method used was descriptive qualitative with a library research approach. The results indicate that the implementation of the Independent Curriculum in early childhood character development is carried out through two main channels: integration into intracurricular activities (play-based learning) and the Pancasila Student Profile Strengthening Project (P5) through contextual themes. Character development in this phase focuses on the six dimensions of the Pancasila Student Profile, tailored to the child's developmental stage. The main supporting factors are teacher creativity and parental involvement, while challenges lie in teacher pedagogical preparedness and limited facilities in some PAUD units.